2017
DOI: 10.1542/peds.2016-2128
|View full text |Cite
|
Sign up to set email alerts
|

A Targeted Approach for Congenital Cytomegalovirus Screening Within Newborn Hearing Screening

Abstract: A targeted CMV approach that tests newborns who fail their NHS identified the majority of infants with CMV-related SNHL at birth. However, 43% of the infants with CMV-related SNHL in the neonatal period and cCMV infants who are at risk for late onset SNHL were not identified by NHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
167
2
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(182 citation statements)
references
References 30 publications
(19 reference statements)
3
167
2
10
Order By: Relevance
“…In total, 68 neonates had congenital CMV, and 24 had confirmed SNHL. Overall, 7/24 (29%) of cases of SNHL in Brazil were attributable to CMV, a figure similar to that reported from other countries . What was different from the published literature was that none of 49 babies in the study with congenital CMV who had normal hearing at birth developed SNHL when followed prospectively with serial hearing tests for a median of 36 months .…”
supporting
confidence: 57%
See 1 more Smart Citation
“…In total, 68 neonates had congenital CMV, and 24 had confirmed SNHL. Overall, 7/24 (29%) of cases of SNHL in Brazil were attributable to CMV, a figure similar to that reported from other countries . What was different from the published literature was that none of 49 babies in the study with congenital CMV who had normal hearing at birth developed SNHL when followed prospectively with serial hearing tests for a median of 36 months .…”
supporting
confidence: 57%
“…CMV is the commonest cause of congenital infection, damages the intellectual potential of as many babies as does Down syndrome, and is the single most common cause of sensorineural hearing loss (SNHL) in children . Performing tests for CMV in those who fail neonatal hearing screening identifies some cases of SNHL but misses the majority, because many CMV cases do not develop SNHL until later in life . Valganciclovir given within a month of birth to babies born with symptoms of congenital CMV infection reduces hearing loss, but this treatment cannot be considered in most cases of congenital infection because only a minority exhibit signs at birth .…”
mentioning
confidence: 99%
“…19 Data from the CMV and Hearing Multicenter Screening Study revealed that nearly half of children with asymptomatic congenital CMV infection who are diagnosed with SNHL within 8 weeks of age are missed by newborn hearing screening. 34 Screening of newborns for congenital CMV infection may allow early identification of SNHL in children with asymptomatic congenital CMV infection 34 so that they can receive appropriate interventions to minimize delays in their communication, cognition, reading, and social-emotional development. 35 However, there is currently no consensus on audiologic monitoring for children with asymptomatic congenital CMV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, infants with asymptomatic infection may account for a greater number of SNHL cases. 4 Moreover, an estimated 5% of children with asymptomatic congenital CMV infection -- about 900 children annually in the United States -- have severe hearing loss in at least one ear by age 12 months. 6 Half of these children meet current candidacy criteria for cochlear implantation by age 5 years.…”
Section: Introductionmentioning
confidence: 99%